How online self-presentation affects well-being and body image: A systematic review. (April 2020) - Bij de Vaate, Nadia A.J.D.; Veldhuis, Jolanda; Konijn, Elly A.
Highlights: How active self-presentation and lurking impact well-being and body image: A review. Results indicate categorizing types of self-presentation, lurking, and well-being. Both self-presentation and lurking can enhance or diminish well-being and body image. Various mechanisms explained differences for self-presentation and lurking types. The social context is important in studying self-presentation and lurking. Abstract: Sophistication of media technologies offers increasing possibilities for selective self-presentation online. However, how self-presentation affects well-being and body image is unclear. This systematic review aimed to map to what extent and under which circumstances types of self-presentation, versus lurking, support or hamper individuals' well-being and body image. Seven scientific databases were searched, comprising 55 relevant studies in 52 publications out of 975 publications. Results were mixed: Both self-presentation and lurking can enhance or diminish well-being and body image. Self-presentation, lurking, and well-being were categorized to systematically clarify results, and vital mechanisms were determined to explain differences within and between self-presentation and lurking. For example, lurking at others generally decreased well-being, whereas authentic self-presentation increased well-being. Moreover, the studies' examined outcomes differed among studies' culture-of-origin. Finally, results showed the importance of peers in examining effects of self-presentation. Future research should delineate self-presentation types, report on cultural variability, and include peer influence.